The suppressive cap-binding complex factor 4EIP is required for normal differentiation - Terrao, Monica; Marucha, Kevin; Mugo, Elisha Muchunga; Droll, Dorothea; Minia, Igor; Falk, Franziska; Clayton, Christine (Nucleic acids research, 2018)
Abstract. Trypanosoma brucei live in mammals as bloodstream forms and in the Tsetse midgut as procyclic forms. Differentiation from one form to the other proce